One Phenomenological Approach to Beauty - Démuth, Andrej; Démuthová, Slávka (European Scientific Journal, ESJ, 2018)
The presented contribution attempts to introduce a phenomenologicalexistential analysis of experiencing beauty (aesthetic experience) through Heidegger’s approach to the examination of state-of-mind. It points out a topic which no doubt extremely interested Heidegger, but which he did not approach by the method he offered in Being and Time. The text thus attempts to reconstruct what Heidegger’s answer to the question “what is beauty?” might have sounded like in this period of his work. The offered analysis respects the original structure of the question regarding the state-of-mind and examines beauty from three viewpoints: 1) what beautiful objects have in common and what characterises them, 2) what characterises aesthetic experience, and finally, 3) what matters to us in an aesthetic experience. Thus it attempts to interpret beauty within Heidegger’s understanding of being and being-in-theworld before the “turn” in his thinking. The study points to the cognitive aspects of aesthetic experience in the sense of understanding beauty as the uncovering of being and the truth of the world.